Implementation of Mosque Economic Business Administration (UEM) Based on PSAK 45 at Masjid Jami Al-Purqon: Efforts Towards Transparency and Economic Empowerment - Gunawan, Wawan; Zahra, Fadila Aulia; Sintia, Kiki; Sari, Rani Puspita; Cahyani, Vini; Kristina, Yunita (Journal of Business, Accounting and Finance, 2025)
Mosque Economic Business (UEM) is one of the activities carried out by mosque managers in order to increase the prosperity of mosques and the people around them. UEM activities require administration to ensure that the financial resources and assets of the mosque are managed effectively and efficiently. The method used in this research is descriptive analysis with the object of researchis Masjid Jami Al-Purqon and the data used is primary. Masjid Jami Al-Purqon is in the Dusun Sindang Taman RT. 05/RW. 07 Cipanas, Tanjungkerta. There are several problems, including limited human resources in managing DKM, loan activities already exist but the implementation is less effective, and administrative records are not in accordance with PSAK. After carrying out the socialization, there were several changes that helped for the financial recording of the Masjid Jami Al-Purqon, including minutes, proof of cash in and proof of cash out of the cash book, as well as financial reports in accordance with PSAK 45. By holding UEM socialization, it is hoped that it can increase public understanding and awareness of the importance of good UEM management and in accordance with sharia principles, so that it can provide optimal benefits for religious and social activities.